আমার জীবন আমার উওম - দেবী, সুপ্রিয়া, ১৯৩৩- (কলকাতা : মডেল পাবলিশিং হাউস, 1999)
Autobiographical reminiscences by a Bengali film actress, with special reference to her husband Uttamakumāra, 1926-1980.
Donated by Akbar Ali Khan
In Bengali.
Keywords: Supriẏā Debī, -- 1933-; Uttamakumāra, -- 1926-1980.; Motion picture actors and actresses -- India -- West Bengal -- Biography